An Empirical Study on Problems Faced By Women Employees in Information Technology Industry with Special Reference to Coimbatore City (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2012)
This paper outlines the various problems faced by women employees in Information Technology industry with special reference to Coimbatore city. The introduction of computer-based technology into clerical work can build on women's skills, and may have given them new opportunities to enhance human skills. But in todays world where a woman wants to support her family financially and is trying to balance her personal and professional life she is facing a lot of problems related to work, their kids and lot of personal problems. There is lot of physical, psychological, medical effects, discrimination at the work and it affects her work as well as family. For the purpose of research the sample of 120 people, who are working in Information Technology industry in Coimbatore has been considered. The primary data has been collected using the questionnaires. Descriptive type of research design & Convenience sampling method has been used. The research work reveals that most of the respondents are facing various physical and psychological problems due to their nature of work. Suggestions have been given, which would help the women employees to overcome their problems.